Pengaruh Laba Akuntansi Dan Earning Per Share (Eps) Terhadap Dividen Kas (Studi pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019) - Riska Maryam Kala; Paulus K. Allolayuk; Cornelia D. Matani (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2021)
Cash dividends are important for investors when investing in a company. Investors tend to prefer dividends because the results obtained are more certain than share capital gains. This study aims to determine the effect of accounting profit and Earning Per Share on cash dividends. The independent variables in this study are accounting profit and Earning Per Share and the dependent variables is cash dividends. The population in this study are manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the period 2015-2019. The sample in this study was 90 samples with 18 companies. The analysis use was descriptive statistics, classical assumption test, multiple regression analysis, and hypothesis testing. Based on the results of the study indicate that partially and simultaneously accounting profit and Earning Per Share have a significant effect on cash dividens. This significant effect indicates that a convincing hypothesis can be accepted. The significant hypothesis explains that high accounting profit and Earning Per Share can increase the amount of cash dividend distribution.